QUALITY AND QUANTITY OF EPHIPIA MOINA MACROCOPA RESULTING FROM MATING USING TILAPIA FISH FECES SUSPENSION FEED - Mubarak & et al., Mubarak x (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The needs of Artemia cysts in Indonesia currently reach ± ​​150 tons / year and all of them are from the imports, so it can become an obstacle in process of hatching fish and shrimp in the future. Increased Culture activities have an impact on increasing fisheries waste production, including fish feces. Fish feces have been proven to be used for the Culture of Moina macrocopa, but have not been tested for the production for ephipia M. macrocopa. This study aims to examine the use of fish aquaculture/feces as feed for the quality and quality of ephipia M. macrocopa. The treatment in this study was the concentration of suspension of tilapia feces 55 mg / L, 64 mg / L, and 73 mg / L and using rice bran suspension feed control 64 mg / L. The results of this study indicate that, the concentration of suspension of tilapia feces does not affect the production and hatching rate of ephipia M. macrocopa. M. macrocopa which was cultured with suspension of tilapia feces produced epiphia production and with a lower hatching rate compared to M. macrocopa with rice bran suspension feed.